Indices of Defective Autophagy in Whole Muscle and Lysosome Enriched Fractions From Aged D2-mdx Mice - Krishna, Swathy; Spaulding, Hannah R.; Quindry, Tiffany S.; Hudson, Matthew B.; Quindry, John C.; Selsby, Joshua T. (Frontiers in Physiology, 2021)
Duchenne muscular dystrophy (DMD) is a fatal, progressive muscle disease caused by the absence of functional dystrophin protein. Previous studies in mdx mice, a common DMD model, identified impaired autophagy with lysosomal insufficiency and impaired autophagosomal degradation as consequences of dystrophin deficiency. Thus, we hypothesized that lysosomal abundance would be decreased and degradation of autophagosomes would be impaired in muscles of D2-mdx mice. To test this hypothesis, diaphragm and gastrocnemius muscles from 11 month-old D2-mdx and DBA/2J (healthy) mice were collected. Whole muscle protein from diaphragm and gastrocnemius muscles, and protein from a cytosolic fraction (CF) and a lysosome-enriched fraction (LEF) from gastrocnemius muscles, were isolated and used for western blotting. Initiation of autophagy was not robustly activated in whole muscle protein from diaphragm and gastrocnemius, however, autophagosome formation markers were elevated in dystrophic muscles. Autophagosome degradation was impaired in D2-mdx diaphragms but appeared to be maintained in gastrocnemius muscles. To better understand this muscle-specific distinction, we investigated autophagic signaling in CFs and LEFs from gastrocnemius muscles. Within the LEF we discovered that the degradation of autophagosomes was similar between groups. Further, our data suggest an expanded, though impaired, lysosomal pool in dystrophic muscle. Notably, these data indicate a degree of muscle specificity as well as model specificity with regard to autophagic dysfunction in dystrophic muscles. Stimulation of autophagy in dystrophic muscles may hold promise for DMD patients as a potential therapeutic, however, it will be critical to choose the appropriate model and muscles that most closely recapitulate findings from human patients to further develop these therapeutics.